(untitled) (International Journal of Nursing Education, 2021)
Physical restraint is generally used in the healthcare setting, implying that students were exposed toit during their clinical placement and may have participated in it, either actively or passively.Thisstudy explores the student nurses’ knowledge and practice of physical restraints in clinical practice.A descriptivequalitative design using one semi-structured individual interview and five focus groupdiscussions on nursing students (N=24) from two higher nursing institutions in Brunei Darussalam.The data were analysed using thematic analysis.We identified three meaningful themes focused on theuse of physical restraint in the hospital setting from the perspective of nursing students, namely, thedefinition of physical restraint, the uses of physical restraint and concerns towards its practice. Thestudent nurses reported that physical restraint was justified in providing safe and high-quality patientcare.However, they have concerns about its practice, both for themselves and the patients. The needfor theoretical and practical guidance onsafe and efficient use of physical restraint may further provideeducational supports to the students.